HUBUNGAN KURANG PERCAYA DIRI TERHADAP INTERAKSI SOSIAL PADA REMAJA KELAS VII DI SMPN 2 CIMAHI - Utami Darojatin, Tresnanda; N Bolla, Ibrahim; W. S, Khrisna (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background: Low self-confidence is an emotional problem that occurs in adolescents and can lead to mental health disorders. In West Java, research results show that 11.2% of adolescents experience emotional mental health problems. In addition, several factors can increase the risk of mental health disorders, such as identity crisis, bullying, and poor relationships with peers and society. These factors can cause adolescents to become less confident. Objective: To determine the relationship between low self-confidence and social interaction among seventh-grade students at SMPN 2 Cimahi. Method: This study is quantitative in nature. The research design is cross-sectional. The population consists of 489 seventh-grade students at SMPN 2 Cimahi, with a sample size of 91 students. The sampling technique used is Proportional Random Sampling. Data analysis includes univariate analysis in the form of frequency distribution and bivariate analysis using the chi-square test. Results: 26.4% of adolescents have moderate levels of low self-confidence, and 73.6% have high levels of low self-confidence. Meanwhile, 15.4% of adolescents have low levels of social interaction, and 84.6% have moderate levels of social interaction. The statistical test results yielded a p-value of 0.017. Conclusion: There is a relationship between low self-confidence and social interaction among seventh-grade students at SMPN 2 Cimahi. Recommendations for teachers, as parental figures at school, are to provide guidance to students to achieve a better quality of life.